The Effect of the Quality of Financial Reporting on the Development of the Level of Quality of Profits Declared in the Financial Reports of Banks Listed on the Palestine Exchange: An Empirical Study - AL TaweeL, Issam M. A. (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2020)
The study aimed to demonstrate the impact of the quality of financial reporting on developing the level of the quality of profits announced in the financial reports of banks listed on the Palestine Stock Exchange. The study relied on a sample of (6) banks listed on the Palestine Stock Exchange during the period (2014-2017). The study developed the level of profits quality as a dependent variable, while the independent variables included accuracy, appropriateness and appropriate timing for financial reporting, and the results of the study showed that there is a positive impact at the level of significance (? ? 0.05) of accuracy on the level of profit quality declared for banks listed on the Palestine Stock Exchange. There is an adverse effect at the level of significance (? ? 0.05) of the suitability and the appropriate timing at the level of the quality of profits declared for the banks listed on the Palestine Stock Exchange. By providing information to its users in a timely manner, otherwise, this information will lose its value, and the need for continuous development of financial reporting reports in light of the emerging and changing needs of users of financial reports or other stakeholders.